Prognostic model of early inflammation development in periodontal tissues by biochemical parameters of oral fluid in patients with orthodontic appliances - I.V. Kovach; O.V. Kopchak; K.A. Buniatian; L.V. Kriachkova; N.V. Alieksieienko; O.Yu. Bindiugin (Medičnì Perspektivi, 2022)
One of the main etiological risk factors and pathogenetic mechanisms for the development of inflammatory diseases of the periodontal disease is a bite pathology or dentofacial anomalies. Therefore, in recent years, scientists make attempts to find new markers that would allow to predict the course of the disease at the preclinical stage of its diagnostics, which would allow to take preventive treatment. In recent years, individual proteins of the mouth, which include matrix metalloproteinases (MMP-8), which can hydrolyze the main proteins in extracellular space and lactoferrin, catelitsidine, KLOTHO protein should be considered leading markers. The purpose is to predict the emergence of early inflammation in periodontal tissues in patients with non-removable orthodontic appliance by studying protein content in the oral fluid in the dynamics of treatment. Among the 113 patients surveyed by us, which underwent orthodontic treatment with non-removable appliance, according to clinical and laboratory studies, 82 people (72,57%) had signs of early inflammation of periodontal tissues. All examined young people were students or students of educational institutions who appealed for advice and treatment to a dental clinic. Biochemical studies of oral fluid and their analysis was conducted at the beginning of orthodontic treatment and 3 and 6 months after the delivery of non-removable orthodontic appliance. The oral fluid was collected in the morning, and the quantitative determination of proteins in it was carried out by the IFA method. In order to assess the probability of prognostication of early inflammation in patients with orthodontic appliance, there was made rank correlation analysis with the determination of the correlation coefficients of the disparity (rs), ROC analysis with the determination of Optimal Cut-Off Point (OСР) – the value of the indicator for prediction and simple and multiple logistic regressions with the calculation of the odds ratio and the construction of a prognostic model (logistics regression equation). For the analysis of factors, on the basis of which it is possible to predict early inflammation of periodontal tissues in patients with orthodontic appliance, a correlation analysis was performed, which showed that the largest changes were in the biochemical parameters of the mouth, namely: MMP-8 (rs=0.58; p<0.001), lactoferin (rs=0.45; p<0.001), catelitsidine (rs= -0.59; p<0.001) and KLOTHO protein (rs= -0.58; p<0.001), with which statistically significant correlations were established. ROC analysis was used to evaluate the discriminatory capacity of the markers investigated, which showed the presence of statistically significant correlations with early signs of inflammatory process in periodontal tissues. As a result of the correlation analysis, it has been found that the most significant changes in the inflammatory process in periodontal tissues were in the biochemical parameters of the mouth, such as MMP-8 (rs=0.58; p< 0.001), lactoferin (rs=0.45; p< 0.001), catholicidine (rs= -0.59; p< 0.001) and Klotho protein (rs= -0.58; p< 0.001), with which statistically significant correlations of average force were detected. The chances of patients with non-removable orthodontic appliance for the development of inflammation in the periodontal tissues are increased by 4.  times.